Moroccan New Green Cities, Towards a Green Urban Transition - Noussaiba Rharbi; Mehmet İNCEOĞLU (Journal of Islamic Architecture, 2022)
Morocco is living in a sustainable transition that touches all the fields. The urban transition seems to take a quick turn, especially after 2014, with the establishment of various eco-cities research projects, eco-neighborhoods, and the construction of green cities such as Benguerir, Bouskoura, and Ze-nata. This paper describes some research into sustainability, the parameters behind green urbanism, and the transition effects. It also explains the Moroc-can urbanism transition witnessed after colonization and the sustainability introduction to the country. This research compares two green cities, Benguerir in the south and Zenata on the Atlantic coast. Both cities are constructed by publicly owned and funded companies, providing a common ground for comparison. This paper analyses sustainability parameters target-ed by the study cases.